2013
DOI: 10.1016/j.ijgo.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Implementing an obstetric ultrasound training program in rural Africa

Abstract: Ultrasound training in a rural setting supported remotely is feasible, efficient, and sustainable. It can help local healthcare workers to screen their prenatal populations for obstetric and neonatal risks, and therefore has the potential to improve outcomes at delivery and provide site-specific epidemiologic data that can be used to develop new healthcare provision strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 20 publications
3
61
0
Order By: Relevance
“…Trainees who completed the course took 3 written and 3 practical tests. In a study by Greenwold et al 1 to assess the feasibility and sustainability of a basic ultrasound training course in rural Africa, 9 nurses and clinical officers in Mozambique were trained in OB ultrasound in a course with 1 week of lectures and 7 weeks of hands-on training. Of the 1744 examinations performed by trainees, 804 were under supervision and 940 without supervision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trainees who completed the course took 3 written and 3 practical tests. In a study by Greenwold et al 1 to assess the feasibility and sustainability of a basic ultrasound training course in rural Africa, 9 nurses and clinical officers in Mozambique were trained in OB ultrasound in a course with 1 week of lectures and 7 weeks of hands-on training. Of the 1744 examinations performed by trainees, 804 were under supervision and 940 without supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that the use of obstetrical (OB) ultrasound in low- and middle-income countries (LMIC) could improve OB management by aiding in identification of high-risk conditions 1, 2, 3, 4, 5. We are participating in a cluster-randomized clinical trial of OB ultrasound under the auspices of the Global Network for Women’s and Children’s Health Research 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that training in ultrasound should be directed towards midwives as well as physicians, as midwives provide most of the maternity care [42]. The effectiveness of training midwives in obstetric ultrasound has been evaluated as successful in several African countries [4345]. In an intervention study conducted in Zambia, 17% of the scans performed by midwives resulted in a change in clinical decision making [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies found psychological benefit for mothers and increased facility utilization associated with obstetric ultrasounds performed during prenatal care [26-28]. Additionally, clinical competence of paraprofessionals (e.g., midwives, paramedics) to perform obstetric ultrasound [29-34] with a relatively short training period has been shown [35,36]. However, the optimal training regimen to reach competency has not been determined.…”
Section: Introductionmentioning
confidence: 99%